RSLSP: An Effective Recovery Scheme for Flash Memory Leveraging Shadow Paging - Alahmadi, Abdulhadi; Chung, Tae Sun (Electronics (Switzerland), 2022)
The flash storage is a non-volatile semiconductor device that is constantly powered and has several advantages such as small size, lower power consumption, fast access, convenient portability, heat dissipation, shock resistance, data retention next to a power off, and random access. Flash memory is presently being incorporated with distinct embedded system devices such as with digital cameras, smart phones, personal digital assistants (PDA), and sensor devices. Nevertheless, a flash memory entails special features such as “erase-before-write” and “wear-leveling”, an FTL (flash translation layer) upon the software layer should be included. Although, the power off recovery plays a significant role in portable devices, most FTL algorithms did not consider the power off recovery scheme. In this paper, we proposed an effective scheme for the recovery of flash memory leveraging the shadow paging concept for storage devices using flash memory. To combat the sudden power off problem, the suggested RSLSP approach saves and keeps the map block data as a combination of two tables, i.e., first is the original block and the second block is a replica for the original one. Our proposed strategy not only improves the capacity of a flash memory device as compared to the state-of-the-art schemes suggested in the literature, but is also compatible with the existing FTL-based schemes.
Keywords: flash memory; next generation; power failure; power of recovery; software-defined architecture; storage management